Features of Formation in the Preschool Age Family’s Submission - Taran, Irina Aleksandrovna (Psychological Prospects Journal, 2013)
In the article different approaches to determination of essence of a concept of a family’s appearance are analyzed. The author analyses different philosophy, psychology and pedagogic approaches to the interpretation of shown and gives his view on the analyzed problem. The features of a family’s appearance in the preschool age, his influence on forming of a child’s outlook are opened up.